Optimization of Charging and Discharging Performance in a PV-Integrated Piston-Based Gravity Energy Storage System - Khin Mar Myint; Wunna Swe (AI Society & STMIK Indonesia, 2026)
The rapid integration of photovoltaic systems into modern power networks has created operational challenges due to their intermittent and fluctuating output. To maintain power balance and enhance grid stability, large-scale and efficient energy storage solutions are essential. This paper presents the dynamic modeling and simulation of a piston-based gravity energy storage system integrated with PV power plant. A detailed MATLAB/Simulink model is developed, including the PV array, power electronic converters, motor–pump system, piston-based gravitational storage mechanism, and generator–load interface. During periods of surplus PV generation, the system operates in charging mode by driving the motor–pump unit to lift the piston, thereby storing energy as gravitational potential. During low PV output, the stored energy is released through the turbine–generator unit to support the load. Simulation results verify stable electrical performance, smooth transition between operating modes, and effective mitigation of PV power fluctuations, demonstrating the technical feasibility of the proposed PGES configuration.